Simulation approach for time-distance calculations based on Newton Forward Divided Difference Interpolation Formula - Sadikin, Zubaidah; Harun, Nurzalina; Panji, Elaziera; Mohd Rohaidi, Nur Nadhirah; Rathi, Sidik; Salim Nasir, Mohd Agos (Academica Press Solutions, 2024)
i-Dash is an innovative application designed to revolutionize the estimation of distance traveled by implementing sophisticated mathematical models such as the Newton Forward Divided Difference Interpolation Formula. By integrating this formula within its graphical user interface (GUI), i-Dash addresses the challenges associated with manually determining optimal routes, offering users enhanced journey experiences and enabling industries to achieve heightened cost, time, and operational efficiencies. Through its utilization of mathematical algorithms, i-Dash dynamically derives a distance function based on time and distance data, providing precise estimations of distance traveled. This approach not only improves the accuracy of estimations but also enhances user experience and facilitates decision-making processes. Leveraging i-Dash's capabilities, users can navigate complex routes with confidence, while industries benefit from optimized logistical planning and resource allocation strategies. Furthermore, i-Dash's innovative approach contributes to advancements in transportation technology and underscores the importance of mathematical modeling in solving real-world problems. The Newton Forward Divided Difference Interpolation Formula has been widely recognized for its effectiveness in estimating functions from discrete data points, making it a suitable choice for i-Dash's distance estimation functionality. Additionally, the significance of graphical user interfaces in simplifying complex tasks and improving user accessibility further validating i-Dash's approach to enhancing journey experiences through its intuitive interface design.